Whole genome duplications have provided teleosts with many roads to peptide loaded MHC class I molecules - Grimholt, Unni (BMC Evolutionary Biology, 2018)
In sharks, chickens, rats, frogs, medaka and zebrafish there is haplotypic variation in MHC class I and closely linked genes involved in antigen processing, peptide translocation and peptide loading. At least in chicken, such MHCIa haplotypes of MHCIa, TAP2 and Tapasin are shown to influence the repertoire of pathogen epitopes being presented to CD8+ T-cells with subsequent effect on cell-mediated immune responses.